Answer:
![\displaystyle average=(1)/(2(e-1))](https://img.qammunity.org/2021/formulas/mathematics/college/jcsj2zasogdi248ifpnamb8ykuor1b3io7.png)
Explanation:
Average Value of a Function
Given a function g(x), we can compute the average value of g in a given interval (a,b) with the equation:
![\displaystyle average=(1)/(b-a)\int_(a)^(b) g(x)dx](https://img.qammunity.org/2021/formulas/mathematics/college/zvhek0xvssqzqdug4hbmpjqdi4smqg2k8j.png)
We use the given data
![\displaystyle average=(1)/(e-1)\int_(1)^(e) (lnx)/(x)dx](https://img.qammunity.org/2021/formulas/mathematics/college/nzjig432aa29wxe10t99bmpe1fpp493yzw.png)
We now compute the indefinite integral with a u-substitution
![\displaystyle I=\int (lnx)/(x)dx](https://img.qammunity.org/2021/formulas/mathematics/college/xkj9gomwlz7eq1adgnhxqlut5j1hql9lv9.png)
We'll use the substitution u=lnx, du=dx/x. Then
![\displaystyle I=\int u.du](https://img.qammunity.org/2021/formulas/mathematics/college/sc7inisrwnulp7b6nn7vek2cp32oosotxj.png)
Integrating
![\displaystyle I=(u^2)/(2)](https://img.qammunity.org/2021/formulas/mathematics/college/np5msr4y3q0a7nd5owob9npbad2f5evwau.png)
Since u=lnx
![\displaystyle I=(ln^2x)/(2)](https://img.qammunity.org/2021/formulas/mathematics/college/uejbe40b52nphpzopef6d1hshr0kslmwku.png)
The average value is
![\displaystyle average=(1)/(e-1)\left|(ln^2x)/(2) \right|_1^e](https://img.qammunity.org/2021/formulas/mathematics/college/wzagy3z4plzuwney3nmh3tnaho3r90wrkd.png)
![\displaystyle average=(1)/(e-1)\left((ln^2e)/(2)-(ln^21)/(2) \right )](https://img.qammunity.org/2021/formulas/mathematics/college/rt7mvbn73valpvi68l8clshm9jsmjlzaoj.png)
Since lne=1, and ln1=0
![\displaystyle average=(1)/(e-1)\left((1)/(2)-0 \right )](https://img.qammunity.org/2021/formulas/mathematics/college/jjfu5x696pfsuqhpi3v0bz25471pfmii00.png)
![\displaystyle average=(1)/(2(e-1))](https://img.qammunity.org/2021/formulas/mathematics/college/jcsj2zasogdi248ifpnamb8ykuor1b3io7.png)